The Psychological Impact of COVID-19 Pandemic on People With Multiple Sclerosis - Motolese, Francesco; Rossi, Mariagrazia; Albergo, Giuliano; Stelitano, Domenica; Villanova, Marialucia; Di Lazzaro, Vincenzo; Capone, Fioravante (Frontiers in Neurology, 2020)
Objective: The coronavirus disease 2019 (COVID-19) has radically changed the world in few weeks. Public health measures as lockdown are necessary to limit the spread of infectious diseases but depriving people of their liberty has negative psychological effects. People with Multiple Sclerosis (PwMS) have a higher burden of neuropsychiatric comorbidities and are known to undertake maladaptive coping strategies in stress conditions. The aim of the present study is to investigate the impact of COVID-19 lockdown on mental health of an Italian cohort of PwMS in comparison with healthy controls (HCs). Methods: A total of 60 PwMS and 50 HCs were asked to answer a web-based survey. This survey enquired about the impact of COVID-19 on patient’s quality of life, job, and daily routine. Mood, fatigue and sleep quality were evaluated using the Beck Depression Inventory II (BDI-II), the Generalized Anxiety Disease 7 (GAD-7), the Fatigue Severity Scale (FSS) and the Pittsburgh Sleep Quality Index (PSQI). Results: Overall, patients had higher scores of BDI, FSS and PSQI and these differences were statistically significant (p < 0.05). When we looked at the subscores of the BDI, we detected a statistically significant difference for the neurovegetative part – that concerns with sleep, appetite, sex, quality of sleep (p < 0.05). One out of five patients reported new symptoms or worsening of known symptom, in particular sensory disturbances and fatigue. When we looked for correlations among variables, we found out that there was a significant relationship between unemployment and BDI total score, GAD-7 and PSQI in MS group. The presence of new symptoms or the worsening of symptoms positively related to FSS and to PSQI. Discussion: We identified that the COVID-19 pandemic had a significant impact on psychological status of PwMS. Compared to the general population, PwMS presented a higher burden of depressive symptoms, a worse sleep quality and perceived an increase in fatigue level, one of the most disabling symptoms of MS. The COVID-19 epidemic poses a challenge to psychological resilience. More studies are warranted to better understand the long-term consequences of the pandemic on mental health of vulnerable people.